Toward morphologically induced anisotropy in thermally hysteretic dielectric properties of vanadium dioxide - Tom G. Mackay; Akhlesh Lakhtakia (AIP Advances, 2022)
The Bruggeman homogenization formalism was used to numerically investigate the dielectric properties of a columnar thin film (CTF) made from vanadium dioxide. For visible and near-infrared wavelengths, the CTF is electromagnetically equivalent to a homogeneous orthorhombic material. Over the 58–72 °C temperature range, the eigenvalues of the CTF’s relative permittivity dyadic are highly sensitive to temperature and vary according to whether the CTF is being heated or cooled. The anisotropy revealed through the eigenvalues and the anisotropy of the associated hysteresis were investigated in relation to temperature for CTFs of different porosities and columnar cross sections. When the free-space wavelength is 800 nm, the CTF is a dissipative dielectric material that exhibits temperature-dependent anisotropy and anisotropic hysteresis. In contrast, when the free-space wavelength is 1550 nm, the CTF can be a dissipative dielectric material, a hyperbolic material, or a metal-like material, depending on the temperature and the porosity of the CTF. As the porosity of the CTF decreases from 0.55 to 0.3, the anisotropy of the CTF becomes more pronounced, as does the anisotropy of the hysteresis. Only relatively modest variations in anisotropy and hysteresis arise in response to varying the columnar cross-sectional shape, as compared to the variations induced by varying the porosity.